Lifting Up the Lives of Extremely Disadvantaged Youth: The Role of Staying in School Longer - Julie Moschion; Jan C. van Ours (Institute of Labor Economics (IZA), 2025)
Using a sample of disadvantaged Australians, we compare trajectories of those who left school before 18 with those who left later, in terms of homelessness, incarceration, substance use and mental health issues. We estimate a staggered difference-in-difference to account for heterogenous treatment effects across cohorts and time. Results indicate that leaving school before 18 increases males' likelihood of experiencing homelessness, being incarcerated, using cannabis daily and illegal street drugs weekly several years after school-leaving. In contrast, for females the difference-in-difference strategy eliminates the correlations between school-leaving age and their outcomes. We also show that while parental separation and other adverse behaviours coincide with early school-leaving, our results are robust to accounting for these, providing support for a causal interpretation of our findings.
Keywords: C23; I12; I24; I32; 330; education; homelessness; substance use; incarceration; mental health; Australia